DIVIDEND POLICY AS STRATEGIC TOOL OF FINANCING IN PUBLIC FIRMS: EVIDENCE FROM NIGERIA - Ashamu, S. O; Abiola, James O.; Bbadmus, S. O (European Scientific Journal, ESJ, 2012)
This is a study on effects of dividend policy on the value of the firms. There are three important decisions a firm must make - investment, financing and dividend decisions. All these decisions are normally made with the aim of achieving the over-riding objectives of firms, which is the maximization of shareholder’s wealth. This study investigated the effect of dividend policy on the value of the firm. It examined relationship between dividend payment and payout ratio, found out the percentage of earnings to be retained or ploughed back into the company and identified the various factors that determine the pricing of shares. Secondary data obtained from Nigeria Stock Exchange Fact book were used for the study. Data obtained were analyzed regression analysis with the aid of Statistical Package for Social Science (SPSS). The study finds out among other thing that the changes in the payout ratio of a company significantly determine the changes in the value of the company. It was therefore recommended in the study that the policy of regular dividend payout should not be changed arbitrarily since it has a serious effect on the investor’s attitude and the financial standing of the organization. The result has a clear implication for investing public, government policy makers and the firm’s management.